Non-governmental Enforcement of EU Environmental Law: A Stakeholder Action for Wolf Protection in Finland - Epstein, Yaffa; Kantinkoski, Sari (Frontiers in Ecology and Evolution, 2020)
The Court of Justice of the EU (CJEU) largely sided with a small Finnish nature protection organization, Tapiola, in a recent judgment that interpreted limitations on the deliberate killing of wolves. Tapiola was able to utilize EU law to bring about both national compliance with EU species protection law and a legal decision that will impact the hunting of wolves and other protected species throughout the EU. Using the Finnish wolf controversy as a case study, this article illustrates how law may be used as a tool for environmental protection in the EU, and the interdependence of environmental NGOs and EU institutions in doing so. It also calls attention to the different roles for NGO stakeholders and different potential outcomes in infringement procedures and references for preliminary rulings.